Studi Deskriptif Teacher Efficacy Guru yang Mengajarkan Critical Thinking di Sekolah Dasar Sekolah Alam Bandung - Fatima Azzahra; Dewi Rosiana (UNISBA Press, 2024)
Abstract. Teachers are required to have 21st century skills, one of which is critical thinking. Teachers who have high self-efficacy tend to be proactive in their approach to increasing knowledge through involvement in various activities, while teachers with low self-efficacy tend to be less involved in various activities because they feel that the efforts given and the need to develop themselves are not related. This study aims to analyze the teacher efficacy of teachers who teach critical thinking at Alam Bandung Elementary School. This study uses a quantitative approach with a descriptive method. The population of the study was teachers at Alam Bandung Elementary School using a total sampling technique of 30 teachers at Alam Bandung Elementary School. The statistical analysis used in this study was descriptive statistics. The results of the statistical analysis showed that the teacher efficacy of teaching critical thinking at Alam Bandung Elementary School was 96.76% in the high category, while 3.30% had a low level of teacher efficacy. Likewise, the three aspects of teacher efficacy, namely; Efficacy for Teaching, Efficacy for Classroom Management, and Efficacy for Student Engagement showed high statistical figures. Thus, the conclusion of this study is that teachers have high self-efficacy in teaching critical thinking to students at Alam Bandung Elementary School. This indicates that teachers at Alam Bandung Elementary School are able to use their self-efficacy in teaching activities in critical thinking. Abstrak. Guru dituntut harus memiliki keterampilan abad-21 salah satunya critical thinking. Guru yang mempunyai self efficacy yang tinggi cenderung proaktif dalam pendekatan mereka terhadap peningkatan pengetahuan melalui keterlibatan dalam berbagai kegiatan, sedangkan guru dengan self efficacy rendah cenderung kurang mempunyai keterlibatan dalam berbagai kegiatan karena merasa bahwa upaya yang diberikan dan kebutuhan dalam mengembangkan diri tidak terkait. Penelitian ini bertujuan untuk menganalisis teacher efficacy guru yang mengajarkan critical thinking di Sekolah Dasar Sekolah Alam Bandung. Penelitian ini menggunakan pendekatan kuantitatif dengan metode deskriptif. Populasi penelitian adalah guru Sekolah Dasar Sekolah Alam Bandung dengan menggunakan teknik total sampling sebanyak 30 orang guru di Sekolah Dasar Sekolah Alam Bandung. Analisis statistik yang digunakan dalam penelitian ini adalah statistik deskriptif. Hasil analisis statistik menunjukkan teacher efficacy yang mengajarkan critical thinking di Sekolah Dasar Sekolah Alam Bandung sebanyak 96,76% berada pada kategori tinggi, sedangkan sebanyak 3,30% memiliki tingkat teacher efficacy rendah. Begitu juga dengan ketiga aspek pada teacher efficacy yakni; Efficacy for Teaching, Efficacy for Classroom Management, dan Efficacy for Student Engagement menunjukkan angka statistik yang tinggi. Dengan demikian simpulan dari penelitian ini adalah guru memiliki self efficacy yang tinggi dalam mengajarkan critical thinking pada siswa di SD Alam Bandung. Hal ini mengindikasikan bahwa guru di SD Alam Bandung mampu menggunakan self efficacy nya pada kegiatan mengajar dalam critical thinking.